Prevalence and antimicrobial resistance patterns of nontyphoidal Salmonella in Ghana: a systematic review and meta‑analysis - Sarkodie‑Addo. P.; Aglomasa. B.C.; Donkor. E.S. (Tropical Medicine and Health, 2025)
Background Nontyphoidal Salmonella (NTS) is a foodborne pathogen of major public health concern, especially in Sub‑Saharan Africa, including Ghana, where it causes invasive infections. However, data on its prevalence, antimi crobial resistance (AMR) patterns, and associated serovars in Ghana are fragmented across multiple studies. Objective This systematic review and meta‑analysis aimed to consolidate data on the prevalence, phenotypic and genotypic antimicrobial resistance profiles of NTS in Ghana. Methods Following PRISMA guidelines, a systematic search was conducted on August 8, 2024, across four data bases: PubMed, ScienceDirect, Scopus, and Web of Science. A total of 31 studies were included. A random‑effects model was used to estimate the pooled prevalence of NTS and the resistance levels of antibiotics reported in two or more studies. Subgroup analysis, multivariate analysis, sensitivity analysis, Egger’s test, and forest plots were per formed to explore variations, assess the influence of individual studies, test for publication bias, and visualize pooled estimates. Results The pooled prevalence of NTS was estimated at 4.69% (95% CI 2.65–8.16) with high heterogeneity observed among the studies (I2 = 98.6%, τ2 = 1.22, τ = 1.10, H = 8.55, Q = 1754.02, p value < 0). Prevalence rates fluctu ated over time: 6.27% (2008–2012), 2.09% (2013–2017), and 7.02% (2018–2023), with no significant trend observed (Q = 2.63, df = 2, p value = 0.27). Antimicrobial resistance (AMR) rates were high, with resistance to trimethoprim sulfamethoxazole (56.7%), amoxicillin/ampicillin (50.8%), tetracycline (46.7%), and ampicillin (36.2%). Cefotaxime had the lowest resistance at 18.6%. Salmonella Typhimurium was the most identified serovar (36.7%), followed by S. Enter itidis (7.9%), S. Rubislaw (4.9%), S. Dublin (3.7%), and S. Kentucky (3.6%). Several AMR genes including gyrA, gyrB, qnrB2, and qnrB19 were identified in human and food samples. Conclusion Despite ongoing interventions, NTS remains a significant public health challenge in Ghana, with high AMR levels. The continued rise in resistance to critical antibiotics highlights the need for a One Health approach, improved diagnostics, enhanced surveillance, and targeted public health measures to control NTS and mitigate AMR.
Research Article
Keywords: Nontyphoidal Salmonella; Salmonellosis; Antimicrobial resistance